Comparative Study on Calculation Standards for Scuffing Load Capacity of Cylindrical Involute Gears - Jia Chenfan; Zhu Caichao; Liu Huaiju; Wei Peitang; Zhu Jiazan; Xu Yongqiang (Jixie chuandong)
The high-end transmission equipment such as the new generation of aero-engines faces the challenge of extreme service environments such as high speed, high temperature and heavy load. Scuffing failure is one of the main failure modes of gears, which seriously affects life and reliability. The common Chinese gear scuffing design standards include GB/Z 6413—2003 and HB/Z 84.4—1984. However, the calculation results of these standards for the scuffing loading capacity of gears are different, and difference exists in the application scope of these formulae. Thus, a comparative study of the cylindrical involute gear scuffing capacity standards based on GB/Z 6413 and HB/Z 84.4 is carried out from three aspects: theoretical analysis, parameter comparison and case studies. For FZG A type gears, dozens of case groups have been calculated. The results show that the calculated average friction coefficient of HB/Z 84.4 is higher than that of GB/Z 6413.2, and the calculated results of HB/Z 84.4 are conservative. It is found that calculation results of the surface temperature of GB/Z 6413.1 and GB/Z 6413.2 are consistent in a large range of torque, oil temperature, and speed. However, the difference in the tooth surface temperature of the two methods becomes larger as the tooth module decreases. The temperature results are generally consistent with each other as the tooth module lies within the range of 4-7 mm.